2022
DOI: 10.3389/fnbeh.2022.933139
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and the development of general mental health problems or attention-deficit hyperactivity disorder (ADHD) symptoms in children and adolescents: A cross-lagged panel analysis of long-term follow-up epidemiological data

Abstract: Studies have shown that physical activity (PA) can provide a helpful, low-risk, and cost-effective intervention for children and adolescents suffering from mental health problems. This longitudinal study aimed to assess whether PA prevents the development of mental health problems, such as attention-deficit/hyperactivity disorder (ADHD) in children and adolescents. Data were analyzed from the German Health Interview and Examination Survey for Children and Adolescents (KiGGS) collected from more than 15.000 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 102 publications
(183 reference statements)
0
4
0
Order By: Relevance
“…Contrary to expectations, we could not find a significant association between long-term trajectories of general mental health problems or ADHD symptoms on the one hand and PA trajectories on the other. In two earlier cross-sectional and longitudinal follow-up studies [29,30], it was shown that high weekly PA may play a protective role concerning general mental health problems and ADHD symptoms. Unfortunately, in our trajectory study there was no trajectory group with a continuously high-level of PA; instead, PA trended to wax and wane.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Contrary to expectations, we could not find a significant association between long-term trajectories of general mental health problems or ADHD symptoms on the one hand and PA trajectories on the other. In two earlier cross-sectional and longitudinal follow-up studies [29,30], it was shown that high weekly PA may play a protective role concerning general mental health problems and ADHD symptoms. Unfortunately, in our trajectory study there was no trajectory group with a continuously high-level of PA; instead, PA trended to wax and wane.…”
Section: Discussionmentioning
confidence: 98%
“…Related to ADHD, cross-sectional and longitudinal follow-up studies have demonstrated that PA may have a positive impact on general mental health problems and ADHD symptoms [29,30], although previous studies have indicated that there is considerable heterogeneity in the developmental course of ADHD symptoms [15,[31][32][33][34][35][36][37][38][39][40][41]. Furthermore, in 1571 children and adolescents (7-15 years old) the growth mixture model for hyperactivity/impulsivity found three classes, different for boys and girls [42].…”
Section: Introductionmentioning
confidence: 99%
“…PA is recognized for its efficacy in regulating physical and mental well-being [ 43 , 75 , 76 ]. In the demanding environment of intensive learning, children might require increased PA to manage psychological stress and emotions, ultimately aiding in reducing CHI [ 77 ]. Intriguingly, while traditionally accepted views propose a negative association between adequate sleep and hyperactivity levels in children, our research results unveiled a notable positive correlation between CSL and CHI among children with PTE.…”
Section: Discussionmentioning
confidence: 99%
“…However, there exists a significant proportion of individuals for whom these treatments are not effective. In this way, physical activity (PA) has been proposed as a promising form of adjunctive treatment for ADHD because it has a positive impact on symptoms of inattention, hyperactivity, and impulsivity in children and adolescents with ADHD (Chan et al, 2022; Christiansen et al, 2019; Ganjeh et al, 2021, 2022; Gapin & Etnier, 2014; Holton & Nigg, 2020; Jeyanthi et al, 2019; Koch et al, 2022; Mercurio et al, 2021; Xie et al, 2021). It should be considered that PA influences the same catecholaminergic systems as stimulant drugs commonly used in the treatment of ADHD (Ben-Amor, 2014; J.…”
Section: Introductionmentioning
confidence: 99%